Stellar activity of evolved, cool giants – old questions revisited. Issue 2 (8th August 2018) - Schröder, K-P; Schmitt, JHMM; Mittag, M; Gómez Trejo, V; Jack, D
ABSTRACT: We present an empirical study of the strength of magnetic stellar activity among cool giant stars on the red and asymptotic giant branches using the Ca ii H&K chromospheric emission strength measured in the context of the Mount Wilson project. Because we consider only stars with a parallax error smaller than 10 per cent, the stars can be accurately placed into an empirical Hertzsprung–Russell diagram and their evolutionary status can be reliably assessed from a comparison with calibrated evolutionary tracks. We find that S -index values among evolved giants redder than 1.5 in B − V and with luminosity classes I and II are larger than those found among the progenitor K giants with luminosity class III and B − V < 1.3. Converting the measured S -indices into physical chromospheric surface fluxes, we find that chromospheric heating undergoes a remarkable reversal and revival as giant luminosity increases. We also discuss possible explanations for this new finding.